ADAPTATION OF SANTRI IN THE ISLAMIC RELIGIOUS EDUCATIONAL CULTURE - Imam Bukhori; Yaqub Cikusin (Journal Education Multicultural of Islamic Society, 2023)
The objectives of the study are to describe, understand and analyze the Islamic religious educational culture at PZH Genggong which includes: the values ​​and customs of Islamic religious educational culture at PZH Genggong; the stages of the adaptation process by new santri in the Islamic religious educational culture at PZH Genggong; and the Multicultural Islamic Education model on the adaptation of santri in Islamic religious educational culture at PZH Genggong. In this study used a qualitative approach with ethnographic methods. Data collection was carried out through participant observation, in-depth interviews and documentation. Data analysis using interactive Miles-Huberman data analysis model and Spradley ethnographic analysis. The results of the study show that the values ​​in PZH Genggong are accumulated in the Satlogi Santri and the Sembilan Budi Utama Santri (Nine Main Virtues of Santri), all of which include in moral, religious and scientific values. These values ​​are then expressed in structured customs of yaumiyyah, usbu'iyyah, syahriyyah, and sanawiyyah. And the process of adaptation of santri in PZH Genggong culture goes through several stages of the process including physical and psychological preparation before boarding (preparation for change), living in boarding school is fun (phase 1 –honeymoon), not feeling at home in boarding school (phase 2 - frustation), the learning to be a good santri (phase 3 - readjustment), and the last is becoming a santri of PZH Genggong (phase 4 -resolution). The multicultural Islamic education model through the process of adaptation of santri to the culture of PZH Genggong consists of the main values ​​that exist in PZH Genggong which are accumulated in the Satlogi Santri and the Nine Main Virtues of Santri, the social structure of PZH Genggong consists of individuals and society, environment and customs, social interaction, the process of adaptation which is the process of adjusting the santri to the values ​​and customs of PZH Genggong, occurs and the social function as the output of the process of adaptation of santri in the culture of PZH Genggong is the transformation of the values ​​of Satlogy Santri and Nine Main Virtues of Santri which is then expressed in the customs of the santri so that there is social harmony in the life of the santri at PZH Genggong.